2004
DOI: 10.1667/rr3211
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Centrosome Separation after DNA Damage: A Role for Nek2

Abstract: DNA damage results in cell cycle arrest in G2. Centrosomes also separate in G2, raising the question of whether separation occurs during the DNA damage-induced G2 arrest. Nek2, the mammalian homologue of NIMA, is a cell cycle-regulated serine/threonine protein kinase that regulates centrosome separation during G2. Here we show that damaged cells fail to activate Nek2. Both Nek2 levels and activity are reduced after DNA damage. Radiation inhibits the premature centrosome splitting induced by overexpression of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 58 publications
1
79
0
Order By: Relevance
“…27 NEK2 promotes centrosome separation at the onset of mitosis and is involved in cell division and mitotic regulation. 47,48 Overexpression of NEK2 induces premature centrosome separation and nuclear defects, which are indicative of mitotic errors. 49 High levels of NEK2 expression are found in seminomas 27 and ductal carcinoma of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…27 NEK2 promotes centrosome separation at the onset of mitosis and is involved in cell division and mitotic regulation. 47,48 Overexpression of NEK2 induces premature centrosome separation and nuclear defects, which are indicative of mitotic errors. 49 High levels of NEK2 expression are found in seminomas 27 and ductal carcinoma of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…44). In addition, it was shown that cells exposed to ionizing radiation exhibit both decreased NEK2 expression and kinase activity, and exposure to ionizing radiation inhibits NEK2-mediated separation of the centrosome (45). Thus, p53-mediated repression of NEK2 could link centrosome inactivation to the DNA damage response network.…”
Section: Discussionmentioning
confidence: 99%
“…AMPPNP, adenosine 5Ј-(␤,␥-imino)triphosphate. increase in apoptosis suggest that Nek2 may be a viable target for the development of novel anticancer drugs (39,40). We determined the structure of a non-activating Nek2 mutant in complex with the pyrrole-indolinone compound SU11652.…”
Section: Bacterial Expression Of Nek2 Constructs and Phosphorylationmentioning
confidence: 99%